The Influence of Network Exposure, Social Influence and Recognition Towards the Adoption of E-commerce in College Students - Isoliani, Ines Etha; Nugraha, Jaka; Ouariach, Fatima Zahra; Ouariach, Soufiane (Journal of Office Administration : Education and Practice, 2024)
This study aims to analyze what factors can influence students to continue using gamification services on the Shopee e-commerce application. The study was conducted on Office Administration students Class of 2020-2023 with a sample of 150 from the total population of 252 students determined using a Krecjie table with a signification level of 0.05. in the process of analyzing research data using Structural Equation Modeling-Generalized Structured Component Analysis (SEM-GSCA) using gamification has a significant positive influence on social influence and recognition. Social influence has a significant positive effect on attitude, besides that recognition also has a significant positive effect on attitude. Furthermore, the attitude has a significant positive effect on continued use intention. This research can able to provide a better understanding, especially on the application of gamification in e-commerce by examining social influence in games and recognition to continue using  the Shopee e-commerce platform.